Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/antiox11102001
|View full text |Cite
|
Sign up to set email alerts
|

Increased Mobile Zinc Regulates Retinal Ganglion Cell Survival via Activating Mitochondrial OMA1 and Integrated Stress Response

Abstract: Retinal ganglion cells (RGCs), the projection neurons of the eye, are irreversibly lost once the optic nerve is injured, which is a critical mechanism of glaucoma. Mobile zinc (Zn2+) levels rapidly increase in retinal interneuron amacrine cells and Zn2+ is then transferred to RGCs via the Zn2+ transporter protein ZnT-3, triggering RGC loss in optic nerve injury. Zn2+ chelation and ZnT-3 deletion promote long-term RGC survival. However, the downstream signaling pathways of Zn2+ in RGCs remains unknown. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…Contrary to our expectations, the results of our study did not demonstrate any modulation of Ca 2+ -induced mitochondrial swelling by Myls22. Likewise, TPEN, a zinc-chelator and OMA1 inhibitor [ 17 , 38 ], was not effective in preventing Ca 2+ -induced mitochondrial swelling. It is tempting to speculate that OPA1 oligomerization can be more essential for maintaining the mitochondrial cristae structure than OPA1 cleavage as demonstrated by the genetically modified MEFs, which were able to maintain a moderate cristae structure with only S-OPA1 expression [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to our expectations, the results of our study did not demonstrate any modulation of Ca 2+ -induced mitochondrial swelling by Myls22. Likewise, TPEN, a zinc-chelator and OMA1 inhibitor [ 17 , 38 ], was not effective in preventing Ca 2+ -induced mitochondrial swelling. It is tempting to speculate that OPA1 oligomerization can be more essential for maintaining the mitochondrial cristae structure than OPA1 cleavage as demonstrated by the genetically modified MEFs, which were able to maintain a moderate cristae structure with only S-OPA1 expression [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that the inhibition of OPA1 GTPase activity by Myls22 is protective against breast cancer growth [ 16 ]. Similarly, inhibition of OMA1 by N,N,N’,N’-tetrakis-(2-pyridylmethyl)ethylenediamine (TPEN) reduced mitochondrial damage induced by optic nerve injury in C57BL/6J mice [ 17 ], suggesting beneficial effects of L-OPA1 under stress conditions. It is important to mention, however, that TPEN’s ability to chelate zinc may have unspecific impacts on mitochondria.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that Ca 2+ -induced mitochondrial swelling stimulates proteolytic cleavage of L-OPA1 in isolated cardiac mitochondria [ 63 ]. Recently, Myls22, an OPA1 inhibitor, and TPEN (N, N, N’, N’-tetrakis(2-pyridylmethyl) ethylenediamine), a Zn 2+ -chelator and OMA1 inhibitor [ 64 ], exhibited protective effects against breast cancer growth [ 65 ] and attenuated mitochondrial damage [ 66 ]. Despite these promising effects, the role of OPA1 and OMA1 inhibition under Ca 2+ -induced mitochondrial swelling is yet to be evaluated.…”
Section: Mitochondrial Membrane Structure and Organizationmentioning
confidence: 99%
“…16 OMA1 in the mitochondrial inner membrane is involved in the proteolysis and downregulation of OPA1 during stress and apoptosis. [17][18][19][20] The mitochondrial inner membrane uncoupling protein, UCP2, is extensively distributed in the spleen, pancreas, heart, lungs, brain, muscles, and kidneys, 21 and it has a high homology with UCP1. Its main function was previously considered to be proton transport from the mitochondrial intermembrane space to the mitochondrial matrix as well as reducing ATP synthesis, but subsequent studies found that UCP2 is involved in regulating fatty acid metabolism, mitochondrial calcium ion transport, and reactive oxygen species (ROS) production.…”
Section: Introductionmentioning
confidence: 99%
“…The mitochondrial inner membrane zinc metalloprotease, OMA1, and the i‐AAA protease, YME1L, are involved in OPA1 processing 16 . OMA1 in the mitochondrial inner membrane is involved in the proteolysis and downregulation of OPA1 during stress and apoptosis 17–20 …”
Section: Introductionmentioning
confidence: 99%